Who's who of Australian women - Lofthouse, Andrea, 1943- (Methuen Australia, 1982)
A collection of biographies of 1425 living Australian women at the time of compilation. Compiled by Andrea Lofthouse ; based on research by Vivienne Smith. Funding was sourced from an International Women's Year grant. Entries are based on questionnaires sent to potential subjects between 1979-1981.